2012
DOI: 10.1111/j.1542-2011.2012.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Ovary Syndrome: A Common But Often Unrecognized Condition

Abstract: Polycystic ovary syndrome (PCOS) affects 5% to 10% of women of reproductive age, with symptoms often presenting during adolescence and young adulthood. It is a condition characterized by (1) hyperandrogenism, (2) oligomenorrhea or amenorrhea, and (3) polycystic ovaries. This syndrome is associated with significant endocrine, metabolic, cardiovascular, reproductive, and psychiatric morbidities. Although the diagnosis of PCOS is based on the presence of at least 2 of the 3 criteria that characterize the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 66 publications
0
52
0
3
Order By: Relevance
“…(2012) conducted a study which showed that PCOS affected 5% to 10% of women of reproductive age . [11] Similarly in a study conducted by Tehrani FR, et al (2011), on reproductive aged women in Tehran, the prevalence of PCOS was found out to be 8.5% . [12] The present study show the presence of oligomenorrhea, obesity, acne and hirsuitism among women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…(2012) conducted a study which showed that PCOS affected 5% to 10% of women of reproductive age . [11] Similarly in a study conducted by Tehrani FR, et al (2011), on reproductive aged women in Tehran, the prevalence of PCOS was found out to be 8.5% . [12] The present study show the presence of oligomenorrhea, obesity, acne and hirsuitism among women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the age of 15 was taken into consideration because it is crucial for the correct diagnosis and it served as the basis for several recently published studies [21,22,23,24,25,26,27,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that 5-10% of women of reproductive age, whereas 15-20% of infertile women were affected by PCOS, with symptoms usually seen after adulthood and adolescence [1,3]. Although it is such a common disease, the pathophysiology of PCOS is still not exactly known and many findings are mostly obtained from studies about polycystic ovarian antral follicles [4].…”
Section: Introductionmentioning
confidence: 98%
“…Polycystic ovary syndrome (PCOS) is the most common gynecological disease in women of reproductive age and it is characterized by hyperandrogenism, multiple ovarian cysts, oligomenorrhea/amenorrhea [1,2]. It was estimated that 5-10% of women of reproductive age, whereas 15-20% of infertile women were affected by PCOS, with symptoms usually seen after adulthood and adolescence [1,3].…”
Section: Introductionmentioning
confidence: 99%